2021
DOI: 10.1088/1748-9326/ac0e66
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of population migration, crop production pattern, and socioeconomic development: evidence from the early 21st century

Abstract: Global crop production and population distributions have undergone great changes under climate change and socioeconomic development, and have drawn considerable public attention. How to explain the similarity of the migration patterns of crop yield and population density for different countries/regions is still uncertain and worth studying. Here, we estimated the similarity between migrations of main crop caloric yield (i.e. maize, rice, wheat, and soybean) and population density using Fréchet distance, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Lv et al (2013) analyzed the spatial pattern of wheat yield using cluster analysis and emphasized the need to address the spatial gap and improve production over time. To identify the factors affecting wheat production, techniques such as the spatial Durbin model (Zhang and Li, 2022), stepwise regression analysis (Zhang et al, 2021), farmer field surveys (Zhang and Li, 2022), and machine learning (Yu et al, 2022) are utilized. The consensus is that the impact of crop yield is multidimensional, and climate factors have the most direct effect on regional differences in yield (Fen et al, 2020;Lin and Shao, 2020;Twizerimana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Lv et al (2013) analyzed the spatial pattern of wheat yield using cluster analysis and emphasized the need to address the spatial gap and improve production over time. To identify the factors affecting wheat production, techniques such as the spatial Durbin model (Zhang and Li, 2022), stepwise regression analysis (Zhang et al, 2021), farmer field surveys (Zhang and Li, 2022), and machine learning (Yu et al, 2022) are utilized. The consensus is that the impact of crop yield is multidimensional, and climate factors have the most direct effect on regional differences in yield (Fen et al, 2020;Lin and Shao, 2020;Twizerimana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [ 11 ] analyzed the spatial pattern of wheat yield using cluster analysis and found that while wheat production is improving in the time dimension, it is also necessary to pay attention to the gap in the space dimension. In the detection of factors affecting wheat production, research techniques mainly include the spatial Durbin model [ 12 ], stepwise regression analysis [ 13 ], farmer field surveys [ 14 ], and machine learning [ 15 ]. A more consistent conclusion is obtained: the impact of a crop yield is multifaceted and three-dimensional [ 16 ]; Climatic factors are the most direct factors affecting wheat yield and causing its regional differences [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have looked at human migration and its relation to climate during the original radiation of humans from Africa [13][14][15], and during prehistory [16][17][18][19][20], but technological innovations may have made human populations less sensitive to environmental conditions than they were during prehistory. For instance, while suitability for agriculture may be a key prerequisite for maintaining high population densities, in recent generations population centers and agricultural centers are growing increasingly decoupled [9,21]. Other papers have looked at the role of interannual-to-decadal climate change in instigating migration and civil conflict [22][23][24][25][26], but it is difficult to connect such episodes of population change to long-term population trends.…”
Section: Introductionmentioning
confidence: 99%